2019
DOI: 10.9734/ajocs/2019/v6i318997
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Study and Biological Activities of Two Medicinal Plants used in Burkina Faso: Lannea velutina A. Rich (Anacardiaceae) and Ximenia americana L. (Olacaceae)

Abstract: Background: Bacterial infections are at the origin of a number of serious pathologies, including meningitis, bronchopneumopathies, typhoid fever and especially diarrhea, which are still a real public health problem for the child population in developing countries. In most of these countries, people use medicinal plants for primary health care. The objective of this study was to determine the content of phenolic compounds, the antioxidant and antimicrobial activity of extracts from two plants used in traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The fruit has a large kernel that contains about 60% in oil [1]. Several studies have been published showing the medicinal potential of this plant, such as for the treatment of the skin [2], as antimicrobial [3], as gastroprotective action [4], and antioxidant activity [5].…”
Section: Introductionmentioning
confidence: 99%
“…The fruit has a large kernel that contains about 60% in oil [1]. Several studies have been published showing the medicinal potential of this plant, such as for the treatment of the skin [2], as antimicrobial [3], as gastroprotective action [4], and antioxidant activity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the leaves, trunk, and root bark of L. velutina are antibacterial, larvicidal, radical-scavenging, and 15-lipoxygenase-inhibiting [14] [15]. Although L. velutina trunk barks have a long history of widespread use and have demonstrated therapeutic benefits [14] [15], their phytochemistry and safety are poorly understood. To develop new pharmaceuticals and ensure the security of herbal drugs generated from this plant, phytochemical screening and safety testing of L. velutina trunk bark extracts are necessary.…”
Section: Introductionmentioning
confidence: 99%